Analysis Efficiency and Accuracy of Company Financial Reports Regarding the Digital Transformation of Accounting Information Systems - Ninuk Riesmiyantiningtias; Hidayat, Rachmat (Universitas Pamulang, 2026)
This study aims to analyse the impact of digital transformation on Accounting Information Systems (AIS) on the efficiency and accuracy of corporate financial reporting. The background to this study is the phenomenon that many medium-sized companies in Indonesia still face obstacles in implementing digital systems optimally. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 125 respondents, consisting of accounting staff, finance managers, and IT staff directly involved in the reporting process. Data analysis was performed using SmartPLS 4.0 software. The results showed that digital transformation had a positive and significant effect on Mediasi (intervening) (path coefficient = 0.452) and reporting accuracy (path coefficient = 0.318). Furthermore, efficiency was also found to mediate the effect of digital transformation on reporting accuracy. These findings confirm the important role of digital transformation in improving the overall quality of financial information.